Relationship between academic performance and the nursing licensure examination of graduates from a city-subsidized university - Soriano, Gil P.
The Local Government Code aims to empower the local government units (LGUs) in running their own affairs including education. The devolution goes through tertiary education. However, to ensure that LGUs are being true to this mission, they should be able to produce graduates who are able to at least pass the licensure examination. This study determined the relationship between the academic performance and nursing licensure examination of graduates of a city-subsidized university, the nursing professional subjects that best predict the outcome of the nursing licensure examination and described the features of the organizational culture that have likely contributed to such outcomes. The study used an explanatory sequential mixed method of Bertallanfy's General System Theory. Academic records of two batches in 2012 and 2013 were used. Key informant interviews with selected university officials, site observations and document analysis were also done. Independent variables included the nursing professional subjects and the dependent variables were the subtests in the licensure examination. Means, standard deviations, Pearson r correlation and Multiple Regression Analysis were used for the quantitative data while content analysis using the system theory was used for the qualitative data. Findings reveal that graduates were average performers in their academics. This was inversely correlated with the nursing licensure examination. This still suggests direct relationship since the grading system in the university ranged from 1.0 to 5.0 where 1.0 is excellent. Critical Appraisal II, Nursing Care Management 104, and Nursing Care Management 106 were significant predictors of performance in the licensure examination. As an organization, the university suffered from fast turnover of leadership and breaking of admission and retention policies. However, despite being an educational organization affected by local government politics, the University was able to maintain a satisfactory performance in the board examination most likely due to strong intrinsic motivation and commitment of the dean and faculty members. Conclusion: Graduate in the city-subsidized university reached average performance in their academics and performed satisfactorily in the licensure examination for nursing. Despite the pressures of local politics, the school was still able to perform satisfactorily probably due to its committed faculty.